Experimental investigation of perforated and non-perforated Delta Winglet Pairs for heat transfer and pressure drop optimization - Yafid Effendi; Syaiful Syaiful; Mohamad Djaeni; Muhammad Untung Zaenal Priyadi (Politeknik Negeri Lhokseumawe, 2025)
This study experimentally investigates the impact of Delta Winglet Pairs (DWPs) on heat transfer and friction factor in a rectangular duct. Configurations varied by the number of DWP pairs (one, two, and three) and the presence of perforations on the winglet. The performance was evaluated using the Nusselt number ratio (Nu/Nu₀) and friction factor ratio (f/f₀), compared to a smooth baseline. Results show that non-perforated DWPs enhanced heat transfer more effectively, with a maximum 27% higher Nusselt number than perforated ones. Increasing the number of DWP pairs improved thermal performance further, aided by higher airflow velocities that enhanced fluid mixing. In terms of pressure loss, the friction factor decreased with increasing velocity, while more DWPs increased pressure drop. Perforated DWPs reduced average friction by 47% compared to non-perforated ones, due to jet flow effects. Evaluation of the Thermal Enhancement Factor (TEF) revealed that although both configurations benefit from higher airflow, non-perforated DWPs achieved a 13.8% higher TEF than the perforated type. These results suggest that while non-perforated DWPs are optimal for maximum heat transfer, perforated DWPs offer a more favourable trade-off when pressure loss must be minimized.